Fundamental study of acute myocardial infarction in young adults: identifying coronary artery disease-specific proteome panel as predictor of early significant coronary atherosclerosis in young adults. - Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Mohamed Bakrim, Norbaiyah (2019)
Acute myocardial infarction (AMI) is the most common clinical manifestation of coronary artery disease (CAD). Hypertension was identified as an important risk factor of AMI at a young age. The identification of CAD biomarkers in these young adults is necessary as a tool for early prediction of CAD. The objective of this study was to investigate protein expression profiles of young adults with AMI. A comparative cross-sectional study was conducted in 160 young adult males aged 18-45 years old (normotensives, prehypertensive, hypertensive and AMI groups). Sample analysis comprised of discovery and verification phases. In the discovery phase, proteins in the pooled plasma samples from 10 AMI patients and 10 controls, were separated by two-dimensional electrophoresis. The protein spots that were expressed differently in AMI patients were identified via MALDI-TOF mass spectrometry. In the verification phase, the plasma concentration of the identified proteins was measured using enzyme-linked immunosorbent assay (ELISA) in all 4 groups. Haptoglobin (Hp) was significantly higher in AMI patients in comparison to all 3 groups. Plasma Hp concentrations were significantly increased in young AMI patients relative to controls, prehypertensive and hypertensive subjects. Hp has a significant role as an inflammatory marker of CAD development in young adults.